Effect of HIV-related knowledge on utilisation of voluntary HIV testing service among university students in Sub-Saharan Africa: a systematic review and meta-analysis protocol. Issue 7 (6th July 2021) - Diress, Gedefaw; Addisu, Amanuel; Endalifer, Melese Linger
Abstract : Introduction: Voluntary HIV testing is a vital preventive measure to reduce HIV transmission. Existing evidence on the association between HIV-related knowledge and HIV testing service utilisation shows inconsistent findings. Therefore, the aim of this review is to assess whether knowledge of HIV is related to improvement in voluntary HIV testing service utilisation among university students in Sub-Saharan Africa. Methods and analysis: A systematic review of studies on the association of HIV-related knowledge and voluntary HIV testing service utilisation among university students will be conducted. We will search several electronic databases, including PubMed/MEDLINE, African Journals Online, Web of Science and Cochrane Library, for all study types looking at the association between HIV-related knowledge and voluntary HIV testing service utilisation. Two reviewers will independently screen all retrieved records and full-text articles and extract data. The Higgins I 2 test will be used to assess heterogeneity between studies. Random-effects meta-analysis will be conducted, if feasible and appropriate. Additional analyses will be performed to explore potential sources of heterogeneity. Stata statistical software (V.14) will be used to analyse the data. Ethics and dissemination: Formal ethical approval is not required because the systematic review relies on primary studies. The results will be disseminated through a peer-reviewed publication, conference presentation and the popular press.